2017
DOI: 10.1038/srep40303
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coronary artery disease and subclinical atherosclerosis related polymorphisms on the risk of atherosclerosis in rheumatoid arthritis

Abstract: A genetic component influences the development of atherosclerosis in the general population and also in rheumatoid arthritis (RA). However, genetic polymorphisms associated with atherosclerosis in the general population are not always involved in the development of cardiovascular disease (CVD) in RA. Accordingly, a study in North-American RA patients did not show the association reported in the general population of coronary artery disease with a series of relevant polymorphisms (TCF21, LPA, HHIPL1, RASD1-PEMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…It has been proposed that NT5C2 regulates the intracellular concentration of inosine 5′-monophosphate and guanosine 5′-monophosphate and the production of UA [14]. NT5C2 also has potential therapeutic importance since it can phosphorylate some anti-tumor and antiviral nucleoside analogs [14, 20, 30]. A previous study implied that NT5C2 influences a reduction in both visceral and subcutaneous fat mass, which relates to CVD morbidity and mortality [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that NT5C2 regulates the intracellular concentration of inosine 5′-monophosphate and guanosine 5′-monophosphate and the production of UA [14]. NT5C2 also has potential therapeutic importance since it can phosphorylate some anti-tumor and antiviral nucleoside analogs [14, 20, 30]. A previous study implied that NT5C2 influences a reduction in both visceral and subcutaneous fat mass, which relates to CVD morbidity and mortality [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these reports were obtained from genome-wide association studies (GWAS) and are not supported by detailed studies. Importantly, few studies have focused on the relationship between NT5C2 polymorphisms and CHD risk [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, elevated TGF-β1 levels and altered downstream signalling have been implicated in the etiology of atherosclerosis 26 , vessel restenosis 27 and in the development of the neointima 28 . Genome-wide association studies have also identified chromosome 14q32 as a locus for a hitherto uncharacterized gene called HHIPL1 (Hedgehog interacting protein-like 1) 29 which encodes a sequence homolog of an antagonist of hedgehog signalling that is secreted as a pro-atherogenic protein to regulate lesion formation 30 .…”
Section: Tgf-β1 Is Released By Both Inflammatory Cells and Vascular Cmentioning
confidence: 99%
“…PEMT rs12936587 variant was associated with increased susceptibility to CAD (OR 1.07, 95% CI 1.05-1.09, p = 4.45x10 −10 ) (Schunkert et al, 2011) in a meta-analysis of 14 GWAS (22,233 cases of CAD and 64,762 controls). However, there was no association with cardiovascular events (IHD, CVA, peripheral arterial disease), and atherosclerosis determined by carotid intima-media wall thickness (IMT) by carotid ultrasonography in a detailed study of 2,609 Spanish individuals (López-Mejías et al, 2017).…”
Section: Genetic Associations Not Discovered Through Genome Wide Assomentioning
confidence: 96%